Problematika Guru dalam Mengembangkan Media Pembelajaran Berbasis Teknologi Informasi di Sekolah Dasar - Onyta Pioma Gabe Pardede; Khairunnisa Khairunnisa (Journal on Education, 2024)
This research is intended to identify and examine the various obstacles faced by teachers in creating information technology-based learning media in elementary schools. The approach applied is a case study and qualitative method. This research involves in-depth interviews with teachers in several regions. The research results show that the main obstacles include a lack of training and technical support, limited technological infrastructure, and resistance to changes in traditional learning methods. Thus, this research provides important insights for educational policy makers in designing strategies for increasing teacher competency and developing technological infrastructure in elementary schools.